Reduction of biofilm adhesion strength by adjusting the characteristics of biofilms through enzymatic quorum quenching. (February 2022) - Wang, Yong-Chao; Wang, Can; Han, Meng-Fei; Tong, Zhen; Hu, Xu-Rui; Lin, Yu-Ting; Zhao, Xin
Abstract: Biofilm adhesion to the surface of a carrier plays an essential role during biofilm formation. Quorum quenching (QQ) has been shown to have great potential for delaying biofouling. However, little is known about whether QQ reduces the adhesion strength of biofilms during the formation process to inhibit biomass accumulation. In this study, we explored the effect of enzymatic QQ on the adhesion strength during biofilm development. In addition, a quantitative method was used to measure the adhesion strength of biofilms based on the shear force of water flow. Experimental results showed that QQ enzyme could reduce the adhesion strength of biofilms by at least 37% compared with the control. Furthermore, the biofilm accumulation rates were 0.05673 and 0.08762 h −1 with and without the QQ enzyme, illustrating a negative effect of QQ enzyme on biofilm accumulation. Specifically, QQ was confirmed to reduce extracellular polymeric substances, decrease the relative hydrophobicity, change the zeta potential by degrading signal molecules, and weaken the adhesion strength of biofilms. The successful reduction of the adhesion strength of the biofilm through QQ could provide a new strategy for the management and regulation of biofilm adhesion in the bioreactor. Graphical abstract: Image 1 Highlights: A method was established to measure the adhesion strength of biofilms. Quorum quenching successfully reduced the biofilm adhesion strength. Quorum quenching can reduce the biofilm-formation rate and thickness.